Ion transport through reconfigurable nanoparticle-surfactant stabilized droplet interface bilayers - Xuefei Wu; Han Xue; Zachary Fink; Zhiqin Xia; Nivedina A. Sarma; Xuchen Gan; John Katsaras; Peter Ercius; Behzad Rad; Brett A. Helms; Paul D. Ashby; Ahmad K. Omar; et al. (Proceedings of the National Academy of Sciences, 2026)
Despite their adaptability and mechanical stability, Pickering emulsions based on the interfacial assembly of colloidal particles have not found use in iontronics, since the dense interfacial packing of micron-sized particles precludes functional connectivity between two droplets. Here, we introduce a chemically reconfigurable droplet interface bilayer (DIB) platform based on the interfacial assembly of nanoparticle-surfactants (NPSs) that enables spontaneous or field-induced formation of ion-conducting nanochannels, eliminating the need of ionophores or nanochannel-forming proteins. These nanoscopic channels emerge from packing defects in the jammed interfacial assemblies of the charged NPSs and support size and charge selective, hysteretic ion transport governed by interfacial electrostatics and dimensional constraints. The NPS-DIBs show short-term and long-term plasticity, hallmarks of neuromorphic behavior, that are mediated by the structural and chemical design of the bilayer. These assemblies establish a versatile, chemically tunable platform that couples soft-matter mechanics with interfacial ionic functionality, offering a robust foundation for soft iontronic systems.